Evaluating the Impact of Information Literacy Workshops on Student Success - Amanda Shannon; Aaron Skira; Ying Chen; Matt Shreffler (Evidence Based Library and Information Practice)
Objective – This study was designed to identify the impact of standalone information literacy tutorials on student success indicators. The study was conducted in two different phases to compare findings across different modalities and to identify whether online, asynchronous delivery of substantively similar content affected outcomes.